Analisis Manifestasi Panas Bumi Melalu Fault Fracture Density (FFD) Di Wilayah Kamojang, Kecamatan Samarang, Kabupaten Garut - Muhammad Faza Syaddad Ar-rafi; Wibowo, Nugroho Budi (Institut Teknologi Nasional Yogyakarta, 2025)
Located on the Pacific Ring of Fire, Indonesia has great potential in significant geothermal energy. Kamojang, located in Samarang District, is one of the areas that show this potential. This study aims to assess the existence of geothermal potential in Kamojang through fault density analysis using the Fault Fracture Density (FFD) method. The data used are fault patterns from the National Digital Elevation Model (DEMNas) which are then analyzed to calculate the density of cracks and presented in the form of contour maps. The resulting FFD values range from -0.5 to 9.5 km/km². The results show that the alignment pattern in Kamojang is mostly northwest - southeast, which is closely related to tectonic movements and the formation of active faults in the area. Although the FFD value in this area is relatively low, the presence of active faults still provides a pathway for the movement of geothermal fluids that form geothermal manifestations such as geothermal craters. These results provide important insights to support the management and development of geothermal energy in the Kamojang area.